Low-cost system for the management of hospital services, applied to hospitalized patients through the use of IoT technology - Auccahuasi, Wilver (2021)
IoT technology is making a strong foray into all work areas, the health sector is not the exception, for this reason many applications are presented more frequently giving solutions to complex problems, thanks to technology a lot of sensitive information is being created that previous years did not It was thought that it could occur, one of them is the creation of databases of medical information, with which applications can be developed based on the exploitation of these data, another type of application is related to the location of certain devices with The intention of locating them in real time, based on this application in this work a methodology is developed to be able to monitor in real time patients admitted to health centers, knowing if they are in their room, also knowing if the patient needs any help with which the nurse on duty can approach to provide assistance. The methodology presents the use of low-cost devices that allow the implementation of IoT solutions, being able to connect 3 rooms through an application developed in LabView that allows knowing the current status of patients, their location and if you need any help, the application can be adaptable to different needs and scalable according to new requirements, it is necessary to indicate that you must have a Wi-Fi connection so that all IoT devices can share the same connection and web services.